Long-term results in hairy cell leukemia treated by splenectomy - Chrobák, L; Podzimek, K; Kerekes, Z; Spacek, J; Voglová, J (Neoplasma, 1993)
Splenectomy as a therapeutic modality has been evaluated in a group of 24 consecutive patients. Before and after splenectomy only supportive therapy was applied with the exception of two patients in whom corticosteroids were administered because of vasculitis. Radiation therapy was applied in one patient because of massive retroperitoneal lymphadenopathy. One patient received Leukeran shortly before the fatal outcome because his response to splenectomy was poor. Out of 24 patients 14 patients died. The median survival for the partial responders and non-responders was 6 months only. Patients with a complete response did not reach median survival yet and 8 of them (33% of the whole group) have been alive for more than 9 years, one patient for more than 20 years. Two distinct groups of patients with respect to the outcome of splenectomy can be distinguished: The first group is characterized by a rapid fatal outcome mostly within two years after splenectomy, the second group has a more favorable course with a plateau and only occasional deaths after the fourth year.
Keywords: Leukocyte Count; senioři; vlasatobuněčná leukemie; analýza přežití; neutropenie; Thrombocytopenia; počet trombocytů; Leukemia, Hairy Cell; Neutropenia; Survival Analysis; výsledek terapie; anemie; Middle Aged; mužské pohlaví; Neutrophils; Adult; Hemoglobins; Anemia; Platelet Count; slezina; Pancytopenia; ženské pohlaví; Humans; neutrofily; lidé středního věku; hemoglobiny; splenektomie; pancytopenie; trombocytopenie; počet leukocytů; Splenectomy; dospělí; Female; Aged; Spleen; Treatment Outcome; lidé; Male